Improvement of Serviceability Level for Presidential Helicopter Type AS332L2 Super Puma Using Part by Hour (PBH) (The Indonesian Journal of Business Administration, 2021)
One of the superior products from PT. Dirgantara Indonesia is AS332L2 Super Puma helicopter that is used as a helicopter for the Indonesian presidency. In supporting the presidential mission to reach remote areas, PT. Dirgantara Indonesia collaborates with the Ministry of the State Secretariat to procure two Super Puma helicopters. The helicopter must be guaranteed serviceability so that it can be used whenever needed. However, the conditions that occurred in the last two years of 2019 and 2020, serviceability from these helicopters is still not optimal. Only 42% in 2019 and 58% in 2020 of the optimal helicopter flying target of 90%. This situation causes helicopters will be grounded and will interfere with the presidential mission.This research aimed to increase the serviceability of the Super Puma helicopter using the Part by Hour method. Based on the analysis, the thing that causes low serviceability is the delay in fulfilling the replacement of helicopter components. Two root causes occur the current poor business model of PBH and the import factor of helicopter components. Based on the results root cause analysis, the possible alternatives that could be made to optimize the acceleration of material arrival to PT. Dirgantara Indonesia and the fulfilment of these materials to customers are to change business model scheme and make additional pooling storage. The alternative solution is estimated to increase the helicopter serviceability according to target expectations, namely by 90%, so that it can contribute to fully supporting the presidential mission in exercising national sovereignty.Keywords: Serviceability, Part by Hour, business model.